Fluoride and thyroid function in children resident of naturally fluoridated areas consuming different levels of fluoride in drinking water: An observational study - Naseemoon Shaik; Raghavendra Shanbhog; B Nandlal; H M Tippeswamy (Wolters Kluwer Medknow Publications, 2019)
Background: Literature shows association between systemic fluorides and endocrine disorders especially related to thyroid, with lack of clarity. Aims and Objectives: The aim and objective of this study was to estimate serum triiodothyronine (T3), thyroxin, thyroid-stimulating hormone (TSH), fluoride, calcium, phosphate, and alkaline phosphatase levels among children with normal nutritional status and optimal iodine intake residing in three different ranges of drinking water fluoride levels. Materials and Methods: The present double-blinded, observational trial comprised of 293 children aged between 9 and 13 years consuming naturally fluoridated water of three different ranges: Group I: 0.01-0.6 parts per million (ppm), Group II: 0.7-1.2 ppm, and Group III: 1.3-1.8 ppm. For each child's demographic data, body mass index and Clinical Fluorosis Index were recorded along with serum T3, T4, TSH, fluoride, calcium, phosphate, and serum alkaline phosphatase levels. Data were analyzed using Chi-square test, Kruskal-Wallis test, and repeated measures ANOVA with SPSS 23. Results: For serum TSH levels, 40% of children in Group I had deranged levels followed by Group III (20%) and Group II (16%). For serum T4 levels, 24% of children of both Groups I and III had deranged levels followed by Group II (20%). Intergroup correlation of drinking water fluoride levels to the number of deranged serum T3, T4, and TSH of the children showed nonsignificant association. Serum T3, calcium, phosphate, and alkaline phosphatase levels in all children showed values falling within normal range. Conclusion: According to the present study results, long-term intake of fluoridated drinking water (0.02-1.4 ppm) did not show effect on the thyroid function in children with normal nutritional status and optimal iodine intake.